Association Between the Neutrophil/Lymphocyte Ratio and Acute Kidney Injury After Cardiovascular Surgery: A Retrospective Observational Study. Issue 43 (October 2015) - Kim, Won Ho; Park, Ji Young; Ok, Seong-Ho; Shin, Il-Woo; Sohn, Ju-Tae
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: A high neutrophil-lymphocyte ratio (N/L ratio) was associated with the development of acute kidney injury (AKI) in patients with severe sepsis. We sought to investigate the association between the perioperative N/L ratios and postoperative AKI in patients undergoing high-risk cardiovascular surgery. A retrospective medical chart review was performed of 590 patients who underwent cardiovascular surgeries, including coronary artery bypass, valve replacement, patch closure for atrial or ventricular septal defect and surgery on the thoracic aorta with cardiopulmonary bypass (CPB). Baseline perioperative clinical parameters, including N/L ratios measured before surgery, immediately after surgery, and on postoperative day (POD) one were obtained. Multivariate logistic regression analysis was used to evaluate risk factors. A total of 166 patients (28.1%) developed AKI defined by the KDIGO (kidney disease improving global outcomes) criteria in the first 7 PODs. Independent risk factors for AKI included old age, decreased left ventricular systolic function, preoperative high serum creatinine, low serum albumin and high uric acid levels, intraoperative large transfusion amount, oliguria, hyperglycemia, and elevated N/L ratio measured immediately after surgery and on POD one. The quartiles of immediately postoperative N/L ratio were associated with graded increase in risk of AKI development (fourth quartile [N/L ratio≥10] multivariate odds ratio 5.90, 95% confidence interval [CI] 2.74–12.73; P < 0.001), a longer hospital stay, and a higher in-hospital and 1-year mortality rate (fourth quartile [N/L ratio≥10] adjusted hazard ratio for 1-year mortality [8.40, 95% CI 2.50–28.17]; P < 0.001). In patients undergoing cardiovascular surgery with CPB, elevated N/L ratios in the immediately postoperative period and on POD one were associated with an increased risk of postoperative AKI and 1-year mortality. The N/L ratio, which is easily calculable from routine work-up, can therefore assist with risk stratification of AKI and mortality in high-risk surgical patients.